(untitled) (Biological Sciences - PJSIR, 1999)
The influence of synthetic surfactant or emulsifierdodecyltrimethyl ammonium-bromide (DoT AB O.4M) on the distribu- tion of sorbic acid (2.5-40mM) was studied in oil (non-aqueous phase) and water (aqueous phase). The study was conducted in two model systems, oil-water, and oil-water-DoTAB (pH 2, temp 25°C). in oil water maximum solubility of sorbic acid in water was 22-28%, while in oil water-Do’T AB the distribution in the aqueous phase was increased to 74-80% due to the presence of surfactant micelles. Foods are multiphase system, where microorganisms exist in the aqueous phase and a large part of sorbic acid is distribute in non-aqueous phase. This investigation suggests that the presence of food emulsifiers in food can increase the distribution of sorbic acid in aqueous phase.